Exome-Wide Association Study Identifies FN3KRP and PGP as New Candidate Longevity Genes. (25th January 2021) - Torres, Guillermo G; Nygaard, Marianne; Caliebe, Amke; Blanché, Hélène; Chantalat, Sophie; Galan, Pilar; Lieb, Wolfgang; Christiansen, Lene; Deleuze, Jean-François; Christensen, Kaare; Strauch, Konstantin; Müller-Nurasyid, Martina; et al.
Abstract: Despite enormous research efforts, the genetic component of longevity has remained largely elusive. The investigation of common variants, mainly located in intronic or regulatory regions, has yielded only little new information on the heritability of the phenotype. Here, we performed a chip-based exome-wide association study investigating 62 488 common and rare coding variants in 1248 German long-lived individuals, including 599 centenarians and 6941 younger controls (age < 60 years). In a single-variant analysis, we observed an exome-wide significant association between rs1046896 in the gene fructosamine-3-kinase-related-protein ( FN3KRP ) and longevity. Noteworthy, we found the longevity allele C of rs1046896 to be associated with an increased FN3KRP expression in whole blood; a database look-up confirmed this effect for various other human tissues. A gene-based analysis, in which potential cumulative effects of common and rare variants were considered, yielded the gene phosphoglycolate phosphatase ( PGP ) as another potential longevity gene, though no single variant in PGP reached the discovery p -value (1 × 10E−04). Furthermore, we validated the previously reported longevity locus cyclin-dependent kinase inhibitor 2B antisense RNA 1 ( CDKN2B-AS1 ). Replication of our results in a French longevity cohort was only successful for rs1063192 in CDKN2B-AS1 . In conclusion, we identified 2 new potential candidate longevity genes, FN3KRP and PGP which may influence the phenotype through their role in metabolic processes, that is, the reverse glycation of proteins ( FN3KRP ) and the control of glycerol-3-phosphate levels ( PGP ).